2018
DOI: 10.1093/icvts/ivy124
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of minimally invasive Ivor Lewis oesophagectomy using the purse string-stapled anastomotic technique in 215 patients with oesophageal carcinoma

Abstract: The incidence of major complications is acceptable for thoracoscopic laparoscopic oesophagectomy with intrathoracic anastomosis using this purse string-stapled anastomotic technique, which is feasible and safe to perform. Some measures designed in the operation will be conducive to reduce the incidence of major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Kan et al . reported that 39 (18.14%) patients had postoperative pulmonary complications after OrVil anastomosis [ 26 ]. The incidence of postoperative pleural effusion in the two groups of patients was 0.2 (2/10) for the OrVil group and 0.75 (18/24) for the overlap group.…”
Section: Discussionmentioning
confidence: 99%
“…Kan et al . reported that 39 (18.14%) patients had postoperative pulmonary complications after OrVil anastomosis [ 26 ]. The incidence of postoperative pleural effusion in the two groups of patients was 0.2 (2/10) for the OrVil group and 0.75 (18/24) for the overlap group.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathoracic anastomotic leakage has been a serious complication after radical resection of esophageal cancer [9,10]. Improper treatment will induce other serious postoperative complications including thoracic infection, empyema, MODS, and septic shock, and can even be life-threatening in severe cases [11,12]. There are many causes of postoperative anastomotic leakage, including the anatomical characteristics of the esophagus itself, such as no serosal covering of the esophagus, longitudinal muscle fibers, and easy tearing at the same direction of suturing and pulling [13], anastomotic blood supply, and anastomotic tension.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The hand-sewn purse-string technique [15][16]: 3-0 suture was used to create a hand-sewn purse string through the muscular layer of the esophagus at least 5 cm proximal to the tumor. A transverse incision was made 2 cm distal to the purse-string suture of the esophagus and the anvil was inserted and fixed by tightening the purse string.…”
Section: Surgery Methodsmentioning
confidence: 99%